Association between body mass index and treatment completion in extended-release naltrexone-treated patients with opioid dependence - Li, Xinyi; Langleben, Daniel D.; Lynch, Kevin G.; Wang, Gene-Jack; Elman, Igor; Wiers, Corinde E.; Shi, Zhenhao (Frontiers in Psychiatry, 2023)
Background: Excessive consumption of opioids is associated with impaired metabolic function including increased body mass index (BMI). Opioid antagonist naltrexone (NTX) is an effective treatment for opioid use disorder (OUD) that has the potential to mitigate such metabolic disturbances. Understanding the relationship between treatment adherence and BMI in NTX-treated OUD patients may provide valuable insights into optimizing clinical outcomes. Methods: Patients with opioid dependence were offered up to three monthly injections of extendedrelease (XR) NTX. Treatment completers (n=41) were defined as those who had received all three XR-NTX injections, and non-completers (n=20) as those missing at least one injection. Logistic regression was performed to examine the association between pre-treatment BMI and treatment completion. Results: BMI was positively associated with treatment completion. This association remained significant after adjusting for potentially confounding variables. Conclusions: Our findings suggest that baseline BMI may serve as a potential predictor of XR-NTX treatment adherence in patients with OUD and could help healthcare providers and policy makers alike in developing strategies to improve retention and tailor interventions for specific patient subgroups.